2014
DOI: 10.1002/em.21910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vivo mutagenicity of isopropyl methanesulfonate in acute and 28‐day studies

Abstract: Understanding the mutagenic dose response could prove beneficial in the management of pharmaceutically relevant impurities. For most alkyl ester impurities, such as isopropyl methanesulfonate (IPMS), little in vivo mutagenicity data exist for dose analysis. The likelihood of a sublinear dose response for IPMS was assessed by comparing the Swain Scott constant, the SN 1/SN 2 reaction mechanism and the O(6) :N(7) guanine adduct ratio to that of more well-known alkyl esters. Based on available information, IPMS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Coffing et al, 2015, reported a NOEL (no-observed-effect level) of 0.25 mg/kg/day for IMS in a 28-day in vivo Pig-a mutation assay in the rat. The authors determined a PDE of 2.5 μg using ICH Q3C methodology and an overall assessment factor of 5000.…”
Section: Toxicological Updatementioning
confidence: 99%
“…Coffing et al, 2015, reported a NOEL (no-observed-effect level) of 0.25 mg/kg/day for IMS in a 28-day in vivo Pig-a mutation assay in the rat. The authors determined a PDE of 2.5 μg using ICH Q3C methodology and an overall assessment factor of 5000.…”
Section: Toxicological Updatementioning
confidence: 99%
“…Mutagenic potency is generally greatest for the iso esters (isopropyl, isobutyl, and isopentyl), being correlated (approximately) with rate of hydrolysis and inversely with Swain–Scott s constant, as shown in Table . [A low Swain–Scott s constant is associated with low alkylation selectivity, greater formation of O 6 -guanyl DNA adducts (compared to compounds with high Swain–Scott s constants that are selective in terms of alkylation at the more nucleophilic N 7 -position of guanine), and higher mutagenic/carcinogenic potency …”
Section: Toxicological Aspects: Mutagenic Activity Of Alkyl Sulfonatesmentioning
confidence: 99%
“…The resulting PDE is 31.8 μg for a 50 kg patient. Coffing et al reported the results of a rat Pig-a assay on isopropyl mesilate (iPrMS) involving daily oral administration at doses of 0.125–2.0 mg/kg/day for 28 days. A threshold dose (NOAEL) of 0.25 mg/kg/day was established, from which a PDE of 2.5 μg can be determined for iPrMS.…”
Section: Toxicologically-based Limits For Alkyl Sulfonatesmentioning
confidence: 99%